The Dynamics of Visitor Experiences in Nightlife Tourism at Nightclubs in Yogyakarta - Fera Dhian Anggraini; Kris Cahyani Ermawati (Politeknik Sahid, 2026)
This study employs a qualitative approach through in-depth interviews and participant observation involving a representative group of visitors. The analysis focuses on various aspects shaping visitor experiences, including social, cultural, and psychological factors. Research Method: This study employs a qualitative approach through in-depth interviews and participant observation involving a representative group of visitors. The analysis focuses on various aspects shaping visitor experiences, including social, cultural, and psychological factors. The findings indicate that visitor experiences are influenced by music, atmosphere, social interactions, nightclub image, and personal satisfaction. These results provide valuable insights for nightclub managers in enhancing the quality of visitor experiences, strengthening the attractiveness of nightlife destinations, and enriching the understanding of social and cultural dynamics within the nightlife context.